2002
DOI: 10.1530/eje.0.1460823
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I, IGF-II, 'free' IGF-I and IGF-binding proteins-2 to -6 during high-dose oestrogen treatment in constitutionally tall girls

Abstract: Objective: To investigate the effect of high-dose oestrogen treatment on IGF-I, IGF-II, free-dissociable IGF-I and the IGF-binding proteins (IGFBP)-2 to -6 in girls with constitutional tall stature. Methods: In patient cohort 1, blood samples were drawn before and after 3 months of daily oral treatment with 0.1 mg ethinyloestradiol. In cohort 2, samples were collected at the end of the treatment period and 3 to 6 months afterwards. IGFs and IGFBPs were analysed by specific immunoassays and by Western ligand bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Circulating IGFBP-6 levels are lower in adult females than males, but oestrogen treatment had no effect on IGFBP-6 levels in constitutionally tall girls [59]. Within the monkey ovary, IGFBPs are expressed in distinctive distributions, with IGFBP-6 mRNA levels being highest in the surface epithelium, similar to that seen in humans [60].…”
Section: A Transgenic Model Of Igfbp-6 Overexpression In the Central mentioning
confidence: 76%
“…Circulating IGFBP-6 levels are lower in adult females than males, but oestrogen treatment had no effect on IGFBP-6 levels in constitutionally tall girls [59]. Within the monkey ovary, IGFBPs are expressed in distinctive distributions, with IGFBP-6 mRNA levels being highest in the surface epithelium, similar to that seen in humans [60].…”
Section: A Transgenic Model Of Igfbp-6 Overexpression In the Central mentioning
confidence: 76%
“…The expression of AR [57,58], BCL2 [57-59], CCND1 [57,58,60], GATA3 [57,58,61,62], IL6ST [57,58], MUC1 [58,63,64], PGR [57,65], SERPINE1 [66,67], HSPB1 [58,68,69] and STC2 [57,58,69,70] have been positively associated with ESR1 expression and/or upregulated by ESR1 . Other studies have found estrogen can directly upregulate transcription of AR [57], GATA3 [57], IGFBP2 [71,72], KRT19 [73], and MUC1 [64], PGR [57,74,75], SERPINE1 [76], HSPB1 [77-79], SERPINA3 [80,81], SERPINE1 [76], and STC2 [57,69,70]. In support of these studies, we also found that the expression of AR, BCL2, GATA3, IL6ST, MUC1, PGR, SERPINE1 , and HSPB1 , were significantly associated with ESR1 expression in AAW; although, only KRT19 and CCND1 were positively correlated with ESR1 levels in American women of Caucasian descent.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies to have evaluated the effect of oestrogens on free IGF-I found that high-dose oestrogen treatment in constitutionally tall girls leads to a considerable decrease in free IGF-I. 25 On the other hand, an ultrafiltration-based assay established that despite an increase in IGFBP-3 proteolysis, adult TS patients undergoing oestrogen therapy did not show significant changes in circulating free IGF-I levels. 20 However, our own assessment of the influence of oestrogen therapy was made in a model along with other variables.…”
Section: Discussionmentioning
confidence: 99%